Effect of zeolite on the nitrogen fertilizer efficiency in rice crop. - Villarreal-Núñez, José Ezequiel; Barahona-Amores, Luís Alberto; Castillo-Ortiz, Ovidio Antonio (Agronomía Mesoamericana, 2015)
The objective of this work was to evaluate the effect of zeolite on the efficiency of nitrogen fertilizer in rice crop. The experiment was conducted in Cacao, Tonosi, Los Santos, Panama, between August and December 2012 and 2013 under rainfed conditions.The Rice variety used was IDIAP FL 106-11 with seeding density of 110 kg/ha in a medium- fertility vertic Fluvisol. This study consisted of five treatments with four replications, following a completely randomized block design using N rate of 80 kg/ha mixed with different percentages of zeolite (0; 15; 25; 35 and 45%). The isotopic technique 15N 3% excess to determine the nitrogen fertilizer use efficiency (EUNF) was used. Each experimental unit consisted of 15 m2 with three micro-plots of 1 m2 where 15N-labeled urea was applied at different times of the crop cycle to determine EUNF in each application. Top grain yields were obtained with 80 kg N + 45% zeolite/ha and 80 kg N + 15% zeolite/ha. A 7% EUNF increase was achieved with the addition of natural zeolite. Small doses of 12 kg/ha (15%) of zeolite can improve EUNF; after subsequent experiments, it is recommended to reduce the amount of N applied in soils with similar soil and climatic conditions suitable for growing rice.